Empirical Approach to Predict Ship Resistance in Level Ice - Koto, Jaswar; Afrizal, Efi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
Prediction of resistance of ship level ice is very important in initial stage of ship design due to related to propulsion and engine power of a ship. As model scale test is very expensive therefore an accurate tool is required to predict the resistance of a ship in ice. A semi empirical method to predict ship resistance in level ice based Koto method was presented. The ship resistance consisted of ice breaking force due to flexural strength of ice, submersion force due to buoyancy, friction force contact between ice and hull and loss momentum force due to collision. The simulation results were verified with experimental data of three icebreakers: MT Uikku, Hellay and Araon. The method was also compared with other empirical methods: Lindqvist, Riska, Keinonen and Jeong. It was founded that the average errors using the proposed method was 3 % for MT Uikku, 0.3 % for Hellay and 0.4 % for Araon.